2020
DOI: 10.3390/cancers12103057
|View full text |Cite
|
Sign up to set email alerts
|

From Conventional Therapies to Immunotherapy: Melanoma Treatment in Review

Abstract: In this review, we discuss the use of oncolytic viruses and checkpoint inhibitors in cancer immunotherapy in melanoma, with a particular focus on combinatory therapies. Oncolytic viruses are promising and novel anti-cancer agents, currently under investigation in many clinical trials both as monotherapy and in combination with other therapeutics. They have shown the ability to exhibit synergistic anticancer activity with checkpoint inhibitors, chemotherapy, radiotherapy. A coupling between oncolytic viruses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 123 publications
0
46
0
Order By: Relevance
“…Nevertheless, metastatic melanoma responds better to immunotherapy compared to conventional chemotherapeutic drugs and radiotherapy [ 63 , 64 , 65 ]. Hence, combined treatment with novel oncolytic adenovirus and ICIs induces complementary antitumor response that could actually lead to more favorable therapeutic outcomes [ 66 , 67 , 68 , 69 ]. Indeed, pre-clinical and clinical findings show that oncolytic vectors can trigger anti-tumor immunity and increase immune cell infiltration (including cytotoxic CD8+ T cells) into the tumor microenvironment (TME).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, metastatic melanoma responds better to immunotherapy compared to conventional chemotherapeutic drugs and radiotherapy [ 63 , 64 , 65 ]. Hence, combined treatment with novel oncolytic adenovirus and ICIs induces complementary antitumor response that could actually lead to more favorable therapeutic outcomes [ 66 , 67 , 68 , 69 ]. Indeed, pre-clinical and clinical findings show that oncolytic vectors can trigger anti-tumor immunity and increase immune cell infiltration (including cytotoxic CD8+ T cells) into the tumor microenvironment (TME).…”
Section: Discussionmentioning
confidence: 99%
“…One of the strategies to enhance the therapeutic efficacy of OVs is their use as primers for other immunotherapies. To this point, genes encoding for immunomodulatory proteins are the most commonly studied for arming oncolytic vectors and have the potential to widen the applications of immuno-oncology (IO) in cancers such as melanoma [ 69 ]. Therefore, we designed a strategy to engineer a newly oncolytic vector AdV-D24-ICOSL-CD40L and investigated its anti-tumor activity in combination with anti PD-1 in in vitro and in vivo immunocompetent mouse model engrafted with murine B16V melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Immune-combination therapies are often used to improve anti-tumor efficacy. In addition to the combination of chemotherapy or targeted therapy with PD-1/PD-L1 inhibitors, promising therapeutic options, such as the combination of oncolytic viruses, have shown anti-tumor activity for patients who fail to respond or achieve durable responses following immunotherapy (102)(103)(104). Oncolytic viruses are tumor specific and have the advantage of triggering anti-tumor immune responses in the tumor microenvironment, so the combination of oncolytic viruses and PD-1/PD-L1 inhibitors may be a useful strategy for future cancer treatment (102)(103)(104).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a randomized placebo-controlled study in stage III patients with CM demonstrated that adjuvant ipilimumab increases relapse-free survival (RFS) and OS. Nevertheless, more than half of patients developed severe side effects (grade 3 or 4) with ipilimumab, and five patients (1.1%) even had a grade 5 outcome [ 23 , 24 , 25 , 26 , 27 ]. As a result of ipilimumab-induced T cell activation, a variety of immune-mediated adverse effects (irAEs) have been observed, particularly including colitis, skin rashes, hepatitis, and less frequently hypophysitis.…”
Section: Immune Checkpoint Inhibitionmentioning
confidence: 99%
“…Large, randomized investigations have demonstrated that mono-nivolumab or -pembrolizumab were superior to mono-ipilimumab. Mono-pembrolizumab in the management of naïve as well as pretreated patients resulted in sustained ORR of 30 to 40% [ 27 , 28 , 29 ]. In previously untreated CM patients, pembrolizumab revealed OS rates of 51% and 41% after three and five years, respectively.…”
Section: Immune Checkpoint Inhibitionmentioning
confidence: 99%